2015
DOI: 10.1080/09593330.2015.1045040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of humic acid in leachate on specific methanogenic activity of anaerobic granular sludge

Abstract: In order to find out the effects of humic acid (HA) in anaerobic-treated landfill leachate on granular sludge, the anaerobic biodegradability of HA as well as the influences of HA on the total cumulative methane production, the anaerobic methanization process and the specific methanogenic activity (SMA) of granular sludge are studied in this paper. Experimental results show that as a non-biodegradable organic pollutant, HA is also difficult to be decomposed by microbes in the anaerobic reaction process. Presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In still another investigation, an analysis of the specific methanogenic activity of granular anaerobic sludge in wastewater containing sodium humate at a concentration of up to 2 g/L showed an increase of this parameter by 19.2% [13]. These results demonstrated that HCs can enhance the metabolic activity of granular sludge.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In still another investigation, an analysis of the specific methanogenic activity of granular anaerobic sludge in wastewater containing sodium humate at a concentration of up to 2 g/L showed an increase of this parameter by 19.2% [13]. These results demonstrated that HCs can enhance the metabolic activity of granular sludge.…”
Section: Discussionmentioning
confidence: 75%
“…It was found that the presence of sodium humate in concentrations up to 2 g/L does not significantly affect the accumulation of CH 4 and even has a certain stimulating effect on the methanogenic activity of anaerobic sludge, which on average is increased by 19% as a result of the buffering and regulating ability of sodium humate [13]. In another study of several methanogenic consortia, partial inhibition of methanogenesis was observed only at an HC concentration of 10 g/L and complete inhibition was shown at 20 g/L HC [14].…”
Section: Introductionmentioning
confidence: 99%
“… 15 The SMA value is calculated by cumulative methane production, and then fitted by one-dimensional linear model. 16 The SMA value was calculated using formula (1) : 17 where k denotes the slope of the fitted line, mL h −1 ; VSS denotes the average concentration of sludge biomass in the culture bottle, mg L −1 ; and V denotes the volume of the mixture, L.…”
Section: Methodsmentioning
confidence: 99%